2011
DOI: 10.1158/0008-5472.can-10-2458
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activation of the Estrogen Receptor-α and Aromatase by the HDAC Inhibitor Entinostat Sensitizes ER-Negative Tumors to Letrozole

Abstract: Approximately 25% of breast cancers do not express the estrogen receptor-a (ERa) and consequently do not respond to endocrine therapy. In these tumors, ERa repression is often due to epigenetic modifications such as methylation and histone deacetylation. For this reason, we investigated the ability of the histone deacetylase inhibitor entinostat (ENT) to trigger reexpression of ERa and aromatase in breast cancer cells, with the notion that this treatment would restore sensitivity to the aromatase inhibitor (AI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 32 publications
1
87
0
2
Order By: Relevance
“…Also, several HDAC inhibitors are assosiated not only with autophagic cell death, but also apoptosis (44,55,70,71,84,97,153). Interestingly, many studies have found that HDAC inhibitors have the ability to convert ER-negative tumors to ER-positive tumors (111,160,161). Finally, a recent study showed that entinostat treatment can prevent the metastasis (143).…”
Section: Resultsmentioning
confidence: 99%
“…Also, several HDAC inhibitors are assosiated not only with autophagic cell death, but also apoptosis (44,55,70,71,84,97,153). Interestingly, many studies have found that HDAC inhibitors have the ability to convert ER-negative tumors to ER-positive tumors (111,160,161). Finally, a recent study showed that entinostat treatment can prevent the metastasis (143).…”
Section: Resultsmentioning
confidence: 99%
“…Protein extracts from TNBC cells were made as described earlier, and 25 mg of protein was analyzed by SDS-PAGE as described previously (16,17). Bands were quantitated by densitometry using ImageJ.…”
Section: Western Blottingmentioning
confidence: 99%
“…Both ER-negative tumors and tumors with acquired resistance treated with entinostat in association with AI have showed a significantly slower growth rate in comparison with those treated with aromatase inhibitors alone in animal models [92,93].…”
Section: Entinostat (Ms-275 Sndx-275)mentioning
confidence: 99%